Patriotic pride as a communication strategy at a moment of crisis - Cabezuelo-Lorenzo, Francisco (Historia y Comunicación Social, 2014)
This article is about confidence and patriotism in contemporary communication campaigns. At this time of crisis, companies need to get back the audience confidence. In the case of Spain, due to the success in sportive competitions, the Santander Bank decides to call for this national feeling and wake up the weak sense of patriotism of Spaniards. After a deep theoretical frame and analysis of the context, this article focuses on the case analysis of a Santander Bank campaign.